The reception of Exodus motifs in Jewish and Christian literature: "Let my people go!" - Kowalski, Beate; Docherty, Susan E. (Themes in biblical narrative, 2022)
The account of the exodus of the Israelite slaves from Egypt under Moses has shaped the theology and community identity of both Jews and Christians across the centuries. Its reception in later scriptures and religious writings, as well as in art and music, continues to inspire liberation movements across the globe. This volume brings together an international group of scholars to explore the re-use of the exodus narratives across a wide range of early Jewish and Christian literature including the Apocrypha and the New Testament. The contributors engage with wider questions of methodology and the impact of social and cultural context on biblical interpretation